Surgical management of lower-grade glioma in the spotlight of the 2016 WHO classification system - Delev, Daniel; Heiland, Dieter Henrik; Franco, Pamela; Reinacher, Peter; Mader, Irina; Staszewski, Ori; Lassmann, Silke; Grau, Stefan; Schnell, Oliver (Journal of Neuro-Oncology, 2019)
Purpose: According to the 2016 WHO classification lower-grade gliomas consist of three groups: IDH-mutated and 1p/19q co-deleted, IDH-mutated and IDH-wildtype tumors. The aim of this study was to evaluate the impact of surgical therapy for lower-grade gliomas with a particular focus on the molecular subgroups. Methods: This is a bi-centric retrospective analysis including 299 patients, who underwent treatment for lower-grade glioma between 1990 and 2016. All tumors were re-classified according to the 2016 WHO classification. Data concerning baseline and tumor characteristics, overall survival, different treatment modalities and functional outcome were analyzed. Results: A total of 112 (37.5%) patients with IDH-mutation and 1p/19q co-deletetion, 86 (28.8%) patients with IDH-mutation and 101 (33.8%) patients with IDH-wildtype tumors were identified. The median overall survival (mOS) differed significantly between the groups (p < 0.001). Surgical resection was performed in 226 patients and showed significantly improved mOS compared to the biopsy group (p = 0.001). Gross total resection (GTR) was associated with better survival (p = 0.007) in the whole cohort as well as in the IDH-mutated and IDH-wildtype groups compared to partial resection or biopsy. IDH-wildtype patients presented a significant survival benefit after combined radio-chemotherapy compared to radio- or chemotherapy alone (p = 0.02). Good clinical status (NANO) was associated with longer OS (p = 0.001). Conclusion: The impact of surgical treatment on the outcome of lower-grade gliomas depends to a great extent on the molecular subtype of the tumors. Patients with more aggressive tumors (IDH-wildtype) seem to profit from more intensive treatment like GTR, multiple resections and combined radio-/chemotherapy.
CRIS-Team Scopus Importer:2023-09-13
Keywords: 1p/19q; Astrocytoma; Gross total resection; IDH-mutation; Lower-grade gliomas; Oligodendroglioma; WHO-classification